Performance evaluation of two pot raised mud improved cookstove - Darlami, Hari Bahadur (Journal of Innovations in Engineering Education, 2021)
Biomass cookstove is widely used in the rural areas of Nepal for cooking and space heating. Its thermal and emission performance keeps importance environmentally, economically and socially. Chimney operated two pot raised mud Improved Cookstove (ICS) is one of Nepal’s most promoted cookstoves. The goal of this study is to evaluate the thermal and emission performance. Thermal and emission performance has been obtained by water boiling test and emission parameters have been measured by using Laboratory Emissions Monitoring System (LEMS). The thermal efficiency of cookstove has been improved from 17.99% to 24.7 % i.e. Tier 1 to 2 with the fabrication of appropriate material and accessories. Similarly total emission performance has been found in Tier 1 and fugitive emission performance has been found in Tier 5. Experimental results of thermal efficiency and fugitive emission complied with the performance target of the cookstove.